2022
DOI: 10.1249/mss.0000000000002977
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular, Respiratory, and Functional Effects of Home-Based Exercise Training after COVID-19 Hospitalization

Abstract: Introduction: The present randomized, single-center, and single-blinded clinical trial tested the hypothesis that tele-supervised homebased exercise training (exercise) is an effective strategy for improving cardiovascular, respiratory, and functional capacity parameters in individuals who were hospitalized due to coronavirus disease 2019 . Methods: Thirty-two individuals (52 ± 10 yr; 17 were female) randomly assigned to exercise (n = 12) or control groups (n = 20) had their anthropometric (weight, body mass i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(81 citation statements)
references
References 35 publications
0
79
1
1
Order By: Relevance
“…HBET yielded a large effect on 30-second sit-to-stand performance (ES: 0.86), whereas PCFS also improved (only in the complete-case analysis) with a moderate magnitude (ES: 0.55). Our results contrast with a previous randomised controlled trial which did not observe any effect of HBET on functional capacity in individuals recovering from COVID-19 hospitalisation 13. Discrepancies in results may be related to the lower severity of the disease during the acute phase, better functional state at baseline and differences in the training protocol, with a less active supervision and unreported adherence in Amaral et al ’s study when compared with the present one 13…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…HBET yielded a large effect on 30-second sit-to-stand performance (ES: 0.86), whereas PCFS also improved (only in the complete-case analysis) with a moderate magnitude (ES: 0.55). Our results contrast with a previous randomised controlled trial which did not observe any effect of HBET on functional capacity in individuals recovering from COVID-19 hospitalisation 13. Discrepancies in results may be related to the lower severity of the disease during the acute phase, better functional state at baseline and differences in the training protocol, with a less active supervision and unreported adherence in Amaral et al ’s study when compared with the present one 13…”
Section: Discussioncontrasting
confidence: 99%
“…Exercise training has been proven an effective non-pharmacological therapy for a broad spectrum of diseases, showing positive effects on cardiovascular, respiratory, skeletal muscle, metabolic and mental disorders 12. In COVID-19, there is preliminary data to suggest that exercise may be of clinical value to individuals previously hospitalised (in wards) by improving cardiovascular (eg, pulse wave velocity) and respiratory (eg, maximal inspiratory and expiratory pressures) parameters 13. However, little is known about the effects of exercise interventions on severe/critical patients, who may be prone to post-exertional symptoms exacerbation.…”
Section: Introductionmentioning
confidence: 99%
“…[32] The findings from current study demonstrated that the telerehabilitation is effective in significantly improving functional capacity, pulmonary function and reducing dyspnea among long COVID individuals. The literature evidenced, exercise delivered via telerehabilitation has led to increase in functional capacity as assessed by the 6 MWT [22][23][24]26] with low level of certainty. However, its effects on dyspnea [22][23][24] and pulmonary functions [22,26] were inconclusive.…”
Section: Resultsmentioning
confidence: 99%
“…[18] Nevertheless, there is limited literature available regarding the impact of telerehabilitation training on exertional tolerance and dyspnea in individuals with Long COVID. [19][20][21][22][23][24][25][26] Apart from the challenges faced in hospital-based training, the ongoing pandemic necessitates clinical and public measures to minimize the risk of viral transmission.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis included 1244 participants (median [IQR] age, 50 [47][48][49][50][51][52][53][54][55][56] years; 45% female participants). Six trials [16][17][18]20,27,29 included patients who had previously been hospitalized due to a COVID-19 infection (range of intensive care unit admission, 6.2%-100%), and 3 trials 19,22,23,30 (4 records) included patients who had not been hospitalized following SARS-CoV-2 infection. Five trials 21,[24][25][26]28 included a mixed population of both patients who had been hospitalized following initial COVID-19 infection and those who had not been hospitalized following initial COVID-19 infection.…”
Section: Description Of the Populationmentioning
confidence: 99%